Flame-retardancy, thermal and coating properties of P-containing poly-acrylate resin cured with MF resin. Issue 1 (4th December 2019) - Liang, Xinyue; Qiao, Hui; Xu, Guilong; Zhang, Yanchong; Liang, Yun; Hu, Jian
Abstract : Purpose: The flammability of poly-acrylate (PA) resin is a major disadvantage in applications that require flame resistance. Many studies, including the authors' previous study, have proved that covalent-incorporated phosphorous-containing (P-containing) monomer onto the PA resin can exhibit better flame resistance than that by an additive approach. However, other properties such as thermal stability, coating properties are still deteriorated. To further improve the flame-retardancy and other comprehensive properties of the P-containing PA resin, in this study, melamine formaldehyde(MF) resin was used not only as a curing agent to enhance the coating properties of the PA resin, but also as a nitrogen-containing (N-containing) resin to form a P-N synergistic effect and therefore further improve its flame retardancy. Design/methodology/approach: Epoxy resin phosphorous acid-modified (EPPA-modified) PA (EPPA-PA) resin was first prepared and then using MF resin as curing agent. The flame retardancy of the cured resin was tested by the limiting oxygen index (LOI) and UL 94 methods. The thermal stability of the cured resin was studied by TGA. The coating technology such as adhesion property, pencil hardness and anti-solvent properties were characterized according to methods of International Standards ISO2409-1992, ISO 15184-1998 and ISO-15184-2012, respectively. The micro-char morphology of the char residue was observed by SEM. Findings: The results showed that by using MF resin as curing agent has provided the PA resin with excellent coating properties and thermal stability, but also gave a P-N synergistic effect which has greatly enhanced the flame retardancy of the cured resin. The cured resin system containing only 1.7 Wt.% P content and 5.3 Wt.% N content can reach a LOI of 26.9 per cent and pass the V-0 rating in the UL-94 test. Research limitations/implications: This resin system releases formaldehyde due to the MF resin. Practical implications: It is expected that the large-scale production of this EPPA-PA resin cured by MF resin system will enable practical industrial applications. Originality/value: This method for the synthesis of a P- and N-containing PA resin system is newfangled.